Circumstantial meanings in behavioral clauses in English and Vietnamese - Tu Trinh, Nguyen Thi; Van Hoa, Phan; Huu Phuc, Tran (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
This article discusses the characteristics of circumstances in behavioral clauses in English and Vietnamese in terms of lexicogrammatical structures and ideational meanings as well as making comparisons of them. Attention has been paid to interpreting a wide range of lexicogrammatical choices as well as various strands of function of circumstances realized by these choices. Each type of circumstances is interpreted (i) structurally, that is, according to rank, and (ii) semantically, according to type. Due to the lexical and grammatical differences between English and Vietnamese, circumstantial elements that are commonly realized by prepositional phrases in English are more likely to be realized by nouns or nominal groups in Vietnamese. As compared with English circumstances, Vietnamese circumstances are less likely to be embedded or encoded in behavioral processes in the clause. Analysis of circumstance characteristics is conducted on twelve English and Vietnamese short stories and novels from the 19th century to present in order to demonstrate the use of circumstances. In the conclusion, we pointed out the new results from our investigation and we will also suggest some practical applications such as the efficient approaches to this domain, solutions to translation matters and language teaching and learning.Received 27th April 2017; Revised 16th October 2017; Accepted 30th October 2017